Rezension von: Schneidmüller, Bernd; Weinfurter, Stefan (Hrsg.), Otto III. - Heinrich II. - Lubich, Gerhard (Württembergisch Franken, 2000)
Bernd Schneidmüller, Stefan Weinfurter (Hrsg.), Otto III. - Heinrich II. Eine Wende? (Mittelalter-Forschungen, Bd. 1), Sigmaringen (Thorbecke) 1997. 438 S., 16 z. T. farbige Abb.